Intracellular phosphate recycling systems for survival during phosphate starvation in plants - Yoshitake, Yushi; Yoshimoto, Kohki (Frontiers in Plant Science, 2023)
Phosphorus (P) is an essential nutrient for plant growth and plants use inorganic phosphate (Pi) as their P source, but its bioavailable form, orthophosphate, is often limited in soils. Hence, plants have several mechanisms for adaptation to Pi starvation. One of the most common response strategies is “Pi recycling” in which catabolic enzymes degrade intracellular constituents, such as phosphoesters, nucleic acids and glycerophospholipids to salvage Pi. Recently, several other intracellular degradation systems have been discovered that salvage Pi from organelles. Also, one of sphingolipids has recently been identified as a degradation target for Pi recycling. So, in this mini-review we summarize the current state of knowledge, including, research findings, about the targets and degradation processes for Pi recycling under Pi starvation, in order to further our knowledge of the whole mechanism of Pi recycling.